A case report of serious haemolysis in a glucose-6-phosphate dehydrogenase-deficient COVID-19 patient receiving hydroxychloroquine. Issue 9 (1st September 2020) - Maillart, E.; Leemans, S.; Van Noten, H.; Vandergraesen, T.; Mahadeb, B.; Salaouatchi, M. T.; De Bels, D.; Clevenbergh, P.
Abstract: While the COVID-19 epidemic occurred since December 2019, as of end April 2020, no treatment has been validated or invalidated by accurate clinical trials. Use of hydroxychloroquine has been popularised on mass media and put forward as a valid treatment option without strong evidence of efficacy. Hydroxychloroquine (HCQ) has its own side effects, some of which are very serious like acute haemolysis in glucose-6-phosphate dehydrogenase (G6PD) deficient patients. Side effects may be worse than the disease itself. Belgian national treatment guidelines recommend the use of HCQ in mild to severe COVID-19 disease. As opinions, politics, media and beliefs are governing COVID-19 therapy, performance of randomised controlled blinded clinical trials became difficult. Results of sound clinical trials are eagerly awaited. We report a case of acute haemolysis leading to admission in intensive care unit and renal failure in a patient with uncovered G6PD deficiency.